(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper presents a neural networks as image processing tools for image compression, present a direct solution method based neural network for image compression. Digital images require large amounts of memory for storage. Thus, the transmission of an image from one computer to another can be very time consuming. By using data compression techniques, it is possible to remove some of the redundant information contained in images, requiring less storage space and less time to transmit. To observe and compare the different algorithms of image compression and Levenberg marquardt is best as compare to other algorithms.